Tattooed Individuals in a Community: Motivations and Identities. Issue 4 (3rd April 2023) - Frankel, Sarah; Childs, Michelle; Kim, Youn-Kyung
ABSTRACT: Expounding upon social identity theory and the extended self-concept, this study examined the role of individuals' motivations to get tattooed and their identities within their feelings of community connectedness. With the growing prevalence of tattooed individuals, antiquated notions of deviant behavior may be transitioning to a broader representation of the tattooed community in academic research. This study was designed with three objectives; first, we examined the effects of tattoo motivations on an individual's self- and group-identity, second, we examined the effects of identities on community connectedness; and finally, we investigated the moderating effects of tattoo coverage on the body in relationship to tattoo motivations and identities. Findings revealed that uniqueness positively influenced group-identity, but not self-identity; spirituality positively influenced both self-identity and group-identity; belongingness positively influenced group-identity, while counter-culture negatively influenced group-identity. Furthermore, both self-identity and group-identity positively influenced community connectedness. Finally, the moderating effects of tattoo coverage existed for two relationships: (a) between uniqueness and self-identity and (b) between spirituality and self-identity.